Corruption and FDI Inflows in Indonesia - Cynthia Yohannaa; Suyanto Suyanto (MediaTrend, 2022)
The inflows of Foreign Direct Investment (FDI) to a country depend on many factorszzne of the crucial factors is the corruption index, which represents a pivotal aspect in Global Investment Competitiveness (GIC). This research analyzes the impact of the corruption perception index on FDI inflows to Indonesia. Other variables affecting FDI are Gross Domestic Product (GDP), inflation rate, and population. Vector Error Correction Model (VECM) is used to estimate the time series sample between 1995 and 2019. Following the time series procedure, several tests are conducted on the dataset before applying VECM: unit-root, optimum lag, and cointegration. The main finding shows that the higher the corruption index, the higher the FDI Inflows, implicating that low corruption attracts more FDI inflows to Indonesia. Other findings are that an increase in GDP attracts more FDI, an increase in inflation rate reduces FDI inflows, and an increase in population increases FDI inflows. The policy implication of the findings is related to an effort in attracting more FDI inflows requires a substantial endeavor in combating corruption and increasing the Corruption Perception Index of Indonesia from time to time.